(untitled) (Journal of Gender and Social Issues, 2016)
This article explores the interplay of female sexuality and patriarchal convergences in Shahraz’, The Holy Woman. Female characters in the novel are found to ’bargain their desires’, either to please their men, or to buy a sense of acceptance within the rigid patriarchal structures of their homes. Kandiyoti’s concept of ’patriarchal bargaining’ is used as a model to understand how and why such women are, forced to comply with male dominance which perpetuates their already gender discriminated position in society. Women are presented as ’objects of desire’ by men, exploited according to their whims, passive recipients of male gaze and are denied the expressions of sexual desire in a male dominated world. This paper concludes that it is precisely through this, bargaining, that female characters such as Zarri Bano, Shahzada and Kaneez are able to achieve a sense of agency but at a greater cost of emotional and sexual exploitation.